PENGARUH - I Komang Widi Adnyana; Ni Putu Ratna Sari; Agung Sri Sulistyawati (Jurnal Kepariwisataan dan Hospitalitas, 2023)
The role of the workforce is one of the main factors that must be considered by the company in achieving its goals. Therefore, in this case the company is required its ability or strength to manage resources in a planned manner, especially human resources as the company's operational implementers to produce useful power and useful results in every activity of the company. Training is one of the processes of self-development to employees in order to work more skilledly and improve employee skills. which in 2018 amounted to 115 d complaints and in 2019 amounted to 347 complaints experienced an increase of 232 complaints. Complaints in 2019 increased from 2018. it can be concluded that there is an increase in complaints due to lack of optimal employee performance due to workforce reduction, irregular training and hight occupancy. The purpose of this research was to find out the effect of training on employee performance in Visesa Village Ubud resort Therefore, there are several types of training which is given by the company such as: proficiency training, repeated training, cross-function training and creativity training. Those training were conducted within specific time period and all employees joined the training. The type of data used in this study is qualitative and quantitative data, sample techniques used are proportional stratified random sampling with the number of respondents obtained, namely 61 respondents. Data analysis techniques used are descriptive quantitative using attitude scale values with intervals of 1 – 4, and simple linear regression analysis. The next data analysis uses descriptive qualitative. The results of the research obtained showed that the training had an effect on performance as evidenced by the tcount value of 4,582 > from t table 1.67. The results showed that the training had a 26.2% effect on employees' work in visesa ubud resort village. The advice that the author can give is that the management conducts regular evaluations of training programs that aim to find out how effective the training program has been done